Pengaruh Lingkungan Sekolah dan Kompetensi Sosial Guru Terhadap Kinerja Guru Serta Implikasinya Terhadap Hasil Belajar Siswa Pada SMK Bidang Manajemen Bisnis Jurusan Pemasaran di Kecamatan Jambi Selatan Kota Jambi - Pratiwi Indah Sari (MENDIDIK: Jurnal Kajian Pendidikan dan Pengajaran, 2020)
The purpose of this research is to know the influence of school environment, social competence, and teacher performance on student learning outcomes at SMK Business Management Department Marketing Department of Jambi Selatan District Jambi City. The population in the study amounted to 65 teachers of economic subjects. Based on the results of research, it can be concluded that in addition there are environments that can menumbuhkembangkan learning process needed competence in socializing from a teacher to his students. This is because, one of the applications of optimal teacher performance can be reflected from the extent to which students are able to implement feedback received when learning activities in the form of better learning achievement.